Evidence-based practice beliefs and implementations: a cross-sectional study among undergraduate nursing students - Nesrin N. Abu-Baker; Salwa AbuAlrub; Rana F. Obeidat; Kholoud Assmairan (BMC, 2021)
Abstract Background Integrating evidence-based practice (EBP) into the daily practice of healthcare professionals has the potential to improve the practice environment as well as patient outcomes. It is essential for nurses to build their body of knowledge, standardize practice, and improve patient outcomes. This study aims to explore nursing students' beliefs and implementations of EBP, to examine the differences in students' beliefs and implementations by prior training of EBP, and to examine the relationship between the same. Methods A cross-sectional survey design was used with a convenience sample of 241 nursing students from two public universities. Students were asked to answer the questions in the Evidence-Based Practice Belief and Implementation scales. Results This study revealed that the students reported a mean total belief score of 54.32 out of 80 (SD = 13.63). However, they reported a much lower implementation score of 25.34 out of 72 (SD = 12.37). Students who received EBP training reported significantly higher total belief and implementation scores than those who did not. Finally, there was no significant relationship between belief and implementation scores (p > .05). Conclusion To advance nursing science, enhance practice for future nurses, and improve patient outcomes, it is critical to teach nursing students not only the value of evidence-based knowledge, but also how to access this knowledge, appraise it, and apply it correctly as needed.